Knowledge integration capability, innovativeness, and entrepreneurial orientation on business performance - Helisia Margahana; Dyah Sugandini (Jurnal Konseling dan Pendidikan)
Objectives – This study aims to analyze the business performance of SMEs in South Sumatera, which has limited resources and is affected by the COVID-19 pandemic but can still survive. The business performance is analyzed through knowledge integration capability, innovativeness, and entrepreneurial orientation.